Fungal Planet description sheets: 469-557 - Crous, Pedro W.; Wingfield, Michael J.; Burgess, Treena I.; Hardy, G.E.St.J.; Crane, Colin; Barrett, Sarah; Cano-Lira, José F.; Le Roux, Johannes J.; Thangavel, Raja; Guarro, Josep; Stchigel, Alberto M.; Martín, María P.; et al. (Westerdijk Fungal Biodiversity Institute, 2016)
Novel species of fungi described in this study include those from various countries as follows: Australia: Apiognomonia lasiopetali on Lasiopetalum sp., Blastacervulus eucalyptorum on Eucalyptus adesmophloia, Bullanockia australis (incl. Bullanockia gen. nov.) on Kingia australis, Caliciopsis eucalypti on Eucalyptus marginata, Celerioriella petrophiles on Petrophile teretifolia, Coleophoma xanthosiae on Xanthosia rotundifolia, Coniothyrium hakeae on Hakea sp., Diatrypella banksiae on Banksia formosa, Disculoides corymbiae on Corymbia calophylla, Elsinoë eelemani on Melaleuca alternifolia, Elsinoë eucalyptigena on Eucalyptus kingsmillii, Elsinoë preissianae on Eucalyptus preissiana, Eucasphaeria rustici on Eucalyptus creta, Hyweljonesia queenslandica (incl. Hyweljonesia gen. nov.) on the cocoon of an unidentified microlepidoptera, Mycodiella eucalypti (incl. Mycodiella gen. nov.) on Eucalyptus diversicolor, Myrtapenidiella sporadicae on Eucalyptus sporadica, Neocrinula xanthorrhoeae (incl. Neocrinula gen. nov.) on Xanthorrhoea sp., Ophiocordyceps nooreniae on dead ant, Phaeosphaeriopsis agavacearum on Agave sp., Phlogicylindrium mokarei on Eucalyptus sp., Phyllosticta acaciigena on Acacia suaveolens, Pleurophoma acaciae on Acacia glaucoptera, Pyrenochaeta hakeae on Hakea sp., Readeriella lehmannii on Eucalyptus lehmannii, Saccharata banksiae on Banksia grandis, Saccharata daviesiae on Daviesia pachyphylla, Saccharata eucalyptorum on Eucalyptus bigalerita, Saccharata hakeae on Hakea baxteri, Saccharata hakeicola on Hakea victoria, Saccharata lambertiae on Lambertia ericifolia, Saccharata petrophiles on Petrophile sp., Saccharata petrophilicola on Petrophile fastigiata, Sphaerellopsis hakeae on Hakea sp., and Teichospora kingiae on Kingia australis. Brazil: Adautomilanezia caesalpiniae (incl. Adautomilanezia gen. nov.) on Caesalpina echinata, Arthrophiala arthrospora (incl. Arthrophiala gen. nov.) on Sagittaria montevidensis, Diaporthe caatingaensis (endophyte from Tacinga inamoena), Geastrum ishikawae on sandy soil, Geastrum pusillipilosum on soil, Gymnopus pygmaeus on dead leaves and sticks, Inonotus hymenonitens on decayed angiosperm trunk, Pyricularia urashimae on Urochloa brizantha, and Synnemellisia aurantia on Passiflora edulis. Chile: Tubulicrinis australis on Lophosoria quadripinnata. France: Cercophora squamulosa from submerged wood, and Scedosporium cereisporum from fluids of a wastewater treatment plant. Hawaii: Beltraniella acaciae, Dactylaria acaciae, Rhexodenticula acaciae, Rubikia evansii and Torula acaciae (all on Acacia koa). India: Lepidoderma echinosporum on dead semi-woody stems, and Rhodocybe rubrobrunnea from soil. Iran: Talaromyces kabodanensis from hypersaline soil. La Réunion: Neocordana musarum from leaves of Musa sp. Malaysia: Anungitea eucalyptigena on Eucalyptus grandis × pellita, Camptomeriphila leucaenae (incl. Camptomeriphila gen. nov.) on Leucaena leucocephala, Castanediella communis on Eucalyptus pellita, Eucalyptostroma eucalypti (incl. Eucalyptostroma gen. nov.) on Eucalyptus pellita, Melanconiella syzygii on Syzygium sp., Mycophilomyces periconiae (incl. Mycophilomyces gen. nov.) as hyperparasite on Periconia on leaves of Albizia falcataria, Synnemadiella eucalypti (incl. Synnemadiella gen. nov.) on Eucalyptus pellita, and Teichospora nephelii on Nephelium lappaceum. Mexico: Aspergillus bicephalus from soil. New Zealand: Aplosporella sophorae on Sophora microphylla, Libertasomyces platani on Platanus sp., Neothyronectria sophorae (incl. Neothyronectria gen. nov.) on Sophora microphylla, Parastagonospora phoenicicola on Phoenix canariensis, Phaeoacremonium pseudopanacis on Pseudopanax crassifolius, Phlyctema phoenicis on Phoenix canariensis, and Pseudoascochyta novae-zelandiae on Cordyline australis. Panama: Chalara panamensis from needle litter of Pinus cf. caribaea. South Africa: Exophiala eucalypti on leaves of Eucalyptus sp., Fantasmomyces hyalinus (incl. Fantasmomyces gen. nov.) on Acacia exuvialis, Paracladophialophora carceris (incl. Paracladophialophora gen. nov.) on Aloe sp., and Umthunziomyces hagahagensis (incl. Umthunziomyces gen. nov.) on Mimusops caffra. Spain: Clavaria griseobrunnea on bare ground in Pteridium aquilinum field, Cyathus ibericus on small fallen branches of Pinus halepensis, Gyroporus pseudolacteus in humus of Pinus pinaster, and Pseudoascochyta pratensis (incl. Pseudoascochyta gen. nov.) from soil. Thailand: Neoascochyta adenii on Adenium obesum, and Ochroconis capsici on Capsicum annuum. UK: Fusicolla melogrammae from dead stromata of Melogramma campylosporum on bark of Carpinus betulus. Uruguay: Myrmecridium pulvericola from house dust. USA: Neoscolecobasidium agapanthi (incl. Neoscolecobasidium gen. nov.) on Agapanthus sp., Polyscytalum purgamentum on leaf litter, Pseudopithomyces diversisporus from human toenail, Saksenaea trapezispora from knee wound of a soldier, and Sirococcus quercus from Quercus sp. Morphological and culture characteristics along with DNA barcodes are provided.
Keywords: ITS nrDNA barcodes; LSU; Novel fungal species; Systematics